Commercial‐Like Self‐Cleaning Colored ZrO2‐Based Bilayer Coating for Remarkable Daytime Sub‐Ambient Radiative Cooling. Issue 10 (10th April 2022) - Liu, Henghao; Kang, Hongjun; Jia, Xin; Qiao, Xianshu; Qin, Wei; Wu, Xiaohong
Abstract: Passive daytime radiative cooling (PDRC) is a low‐carbon energy technology to early achieve the "carbon neutrality" goal. Developing the commercial‐like colored PDRC coatings with sub‐ambient cooling performance is still a big challenge. Herein, a colored bilayer ZrO2 ‐PVDF PDRC coating with sub‐ambient cooling performance, self‐cleaning, and good weather resistance property is first reported. The colored bilayer coating is composed of a thick ultra‐white ZrO2 ‐PVDF reflective layer ( R solar = 0.984) and a thin colorful layer. The obtained red bilayer ZrO2 ‐PVDF PDRC coating has a high solar reflectance ( R solar = 0.950), which could realize the maximum temperature drop of 3.0 °C, and the calculated theoretical cooling power is as high as 131.66 W m −2, showing a good sub‐ambient cooling performance. Furthermore, they show a good self‐cleaning property. Meanwhile, the accelerated aging tests prove that they have a good weather resistance. This work provides a low‐cost, simple, and large‐scale method to prepare the commercial‐like colored PDRC coatings with the sub‐ambient cooling performance, showing a great practical application value. Abstract : This work first reports a colored bilayer ZrO2 ‐PVDF passive daytime radiative cooling (PDRC) coating with sub‐ambient cooling performance, self‐cleaning, and good weather resistance property. The obtained red bilayer ZrO2 ‐PVDF PDRC coating has a high solar reflectance ( R solar = 0.950), which could realize the maximum temperature drop of 3.0 °C, showing a great practical application value in daytime sub‐ambient radiative cooling.